Study on the effect of alkali activated slag cement solidification on dredging sediment - Xu Yanping; Li An; Fan Zhihong (E3S Web of Conferences)
The massive dredging of silt and soft soil has caused serious environmental problems. Carrying out the resource utilization of silt can turn waste into treasure, improve the utilization rate of solid waste, and achieve the goal of energy conservation, emission reduction, and efficiency improvement. The solidification of dredged sediment with a moisture content of 50% was carried out using pure cement, cement+mineral powder, cement+mineral powder+alkali activator, and the effect was compared based on the 28 day unconfined compressive strength of the solidified soil as the main indicator. The results showed that the strength of cement-based solidified soil with composite mineral powder was significantly higher than that of pure cement solidified soil, and the unconfined compressive strength of solidified soil at 28 days was the highest when the mineral powder content was 6%; The strength of alkali activated mineral powder cement stabilized soil is significantly higher than that of cement-based stabilized soil. The contribution of alkali activators to the strength of stabilized soil is ranked in descending order as lithium silicate>sodium silicate>potassium silicate. However, considering the overall cost, sodium silicate is the better choice, and when the modulus of alkali activator is 1.2 and the dosage is 5%, the unconfined compressive strength of stabilized soil at 28 days is the highest.